(untitled) (Medical Forum Monthly, 2024)
Background: Culture is a learned behavior. It is a community’s knowledge and set of practices that evolves out of continuous interactions with the outer environment feedback either positive or negative. In a strict sense culture is a man-made nature opposite to physical nature to survive. Objective: The objective of the study was to investigate the interrelationship of older persons’ (OPs) marital status and mode of living with their medical history. Study Design: Cross Sectional Study Place and Duration of the Study: The study was conducted on behalf of Help Age Pakistan. The data collection was done in various union councils of Rawalpindi city. The study duration was three months and lasted from Sep-2013 to Dec-2013. Materials and Methods: Structured questionnaire was developed to collect information on Older Persons’ health, economic and psychological status. In this regard, an extensive questionnaire was designed and pre-tested vigorously. Questionnaires were filled by the graduates of PMAS-Arid Agriculture University. Results: The respondents who were single were mostly heart patients (n=14, 21.4%). The married respondents reported other diseases that included mental health, skin problems, paralysis, eye and hearing impairments and TB etc (n=704, 20.7%). Widows and widowers were in the third category with the same problems reported in second category (n=274, 20.1%). Results in the category of hypertension explain that elder peoples living in their own houses reported 9.1% hypertension, OPs living in rented houses suffering from hypertension were 10.3%, in case of hired residence percentage recorded was 0.0% and in the other category of living like living with relatives, friends or any other, 14.3% OPs were fighting with hypertension in their lives. Conclusion: The data reveal that OPs living single are likely to catch heart problems, the married OPs were suffering from mental illnesses, dermatological problems, paralysis as well as hearing and visual impairments. The results show that OPs living in their own houses were better off than the ones living in other mode of living. Rented houses reported high percentiles of hypertensions, heart problems, and diabetes.